(untitled) (PANGEEA, 2025)
ABSTRACT. The paper presents some aspects regarding the methods and materials used to combat humidity in heritage buildings. It is known that the moisture in a wall reaches variable heights according to the physical characteristics of the masonry (depending on the porosity and capillary sizes). Taking into account these characteristics, some solutions for improving the masonry of buildings are presented. Thus, some details regarding the interventions at the building foundation level are exposed. At the same time, some materials used for wall ventilation as well as the BIS system for dehumidifying the floor and wall support are presented. The result of the study emphasize that the method which uses ventilation holes to dry masonry can only be applied when we are not dealing with a wetting due to a capillary increase from a water table.